Exploring Greek myth - Clark, Matthew (Chichester, England : Wiley-Blackwell, 2012)
Exploring Greek Myth offers an extensive discussion of variant forms of myths and lesser-known stories, including important local myths and local versions of PanHellenic myths. Clark also discusses approaches to understanding myths, allowing students to gain an appreciation of the variety in one volume.
Chapter One: The Knife Did It: Definitions and Characteristics for the Study of Myth -- Chapter Two: Six Hundred Gods: Greek Myth and Greek Religion -- Chapter Three: Homer's Beauty Pageant: The Traditions of Myth -- Chapter Four: Pelops Shoulder: Sources for the Study of Myth -- Chapter Five: Ikaros Wings, Aktaion's Dogs: Myth and Meaning -- Chapter Six: The Bones of Orestes: Heroes in Myth and Society -- Chapter Seven: Born from the Earth: Founders of Cities and Families -- Chapter Eight: The Judgment of Paris: Comparative Myth -- Chapter Nine: Boys in Dresses, Brides with Beards: Myth and Gender -- Chapter Ten: Agamemnon 's Mask? : Myth and History -- Chapter Eleven: Orestes on Trial: Myth and Thought -- Chapter Twelve: Plato and the Poets: Philosophy and Myth -- Chapter Thirteen: Conclusion
Includes bibliographical references.
Keywords: MYTHOLOGY, GREEK